How does the air pollution prevention and control action plan affect sulfur dioxide intensity in China? - Niu, Shuhai; Chen, Yidong; Zhang, Ruiwen; Feng, Yanchao (Frontiers in Public Health, 2023)
China has taken many regulatory measures since 2013 as part of the Air Pollution Prevention and Control Action Plan (APPCAP) to reduce air pollution in key areas. However, the impacts of APPCAP on sulfur dioxide intensity have received scant consideration in the existing research. Based on the data from 271 prefecture-level cities between 2008 and 2018, the difference-in-differences model is used to explore the effect of it on sulfur dioxide intensity in our study, and several significant results are as follows: (1) Baseline result indicates that pilot cities have experienced a 23% decrease in sulfur dioxide intensity compared to non-pilot cities. (2) The total factor productivity fails to play a partial mediating role in reducing the sulfur dioxide intensity under the implementation of the policy. (3)  Policy still exerts significant adverse effects on sulfur dioxide intensity in the pilot areas of the carbon emission trading scheme according to the results of the triple differences model.